A PCR Detection Method for Rapid Identification of Paenibacillus larvae - Govan, V. A. (American Society for Microbiology, 1999)
American foulbrood is a disease of larval honeybees (Apis mellifera) caused by the bacterium Paenibacillus larvae. Over the years attempts have been made to develop a selective medium for the detection of P. larvae spores from honey samples. The most successful of these is a semiselective medium containing nalidixic acid and pipermedic acid. Although this medium allows the growth of P. larvae and prevents the growth of most other bacterial species, the false-positive colonies that grow on it prevent the rapid confirmation of the presence of P. larvae. Here we describe a PCR detection method which can be used on the colonies that grow on this semiselective medium and thereby allows the rapid confirmation of the presence of P. larvae. The PCR primers were designed on the basis of the 16S rRNA gene of P. larvae and selectively amplify a 973-bp amplicon. The PCR amplicon was confirmed as originating from P. larvae by sequencing in both directions. Detection was specific for P. larvae, and the primers did not hybridize with DNA from closely related bacterial species.